The Implementation of Auction Cancellation as a Legal Remedy for Auction Execution Under Law No. 4 of 1996 - Toguan, Zulfikri; Anggraini, Desra (Yayasan Pendidikan Islam Almatani, 2025)
The issues arising in the implementation of auction cancellation and the sale of auctioned objects based on mortgage rights are related to objections or lawsuits from the debtor, as well as objections from the debtor regarding the auction carried out by the creditor through an auction house. The research questions in this research includes: 1) How is the implementation of auction cancellation as a legal remedy for objections against the auction process according to Law No. 4 of 1996, and 2) What are the obstacles in the implementation of auction cancellation as a legal remedy for auction execution under Law No. 4 of 1996. To address these issues, this research employs a sociological empirical method, where the researcher conducts field research to obtain both primary and secondary data relevant to the research topic. The research is descriptive, aiming to describe the research findings by analyzing statements clearly, in detail, and comprehensively. Based on the research findings, the implementation of auction cancellation and the examination process in the auction involves several stages, such as registration, submission, examination, proof, and decision. On the other hand, obstacles faced in the implementation of auction cancellation include rejection by the defendant, the sale of auctioned objects, and execution.